PENGARUH COMPUTER SELF-EFFICACY TERHADAP KUALITAS SISTEM, KUALITAS INFORMASI, KUALITAS LAYANAN, PENGGUNAAN, KEPUASAN PENGGUNA, DAN DAMPAK INDIVIDU - Suharno Pawirosumarto; Purwanto S. Katidjan; Angga Dwi Mulyanto (MIX: JURNAL ILMIAH MANAJEMEN, 2015)
Abstract: The study aims to determine the effect of computer self-efficacy (CSE) on the qualitysystem, the quality of information, quality of service, usage, satisfaction and impact of individualusers by using a model of success Delone and McLean information systems. The studyconducted on students of system users of e-learning in higher education. The population used inthis study amounted to 144 686 students with a total sample of 178. The sampling method usingproportional random sampling. The analysis tool used is the Generalized Structured ComponentAnalysis (GSCA). The results showed that CSE significant effect on the quality system, thequality of information, quality of service, usage and impact of the individual. Quality systemshave a significant effect on the quality of information, usage, and user satisfaction. The qualityof information significantly influence the use and user satisfaction. Service quality significantlyinfluence the use and user satisfaction. User satisfaction significantly influence the individualimpact. The results also show that the better CSE students will further improve system quality,information quality, service quality, use, and impact of the individual. The better the students'perceptions of the quality system, the quality of information, and the quality of service willincrease the usage and user satisfaction. The better use will have an impact on user satisfaction,so that will have an impact on individual performance.Keywords: Computer Self-Efficacy (CSE), Quality Systems, Information Quality, ServiceQuality, Use, User Satisfaction and Individual Impact.